2021
DOI: 10.3389/fpsyt.2021.699740
|View full text |Cite
|
Sign up to set email alerts
|

Brexanolone, a GABAA Modulator, in the Treatment of Postpartum Depression in Adults: A Comprehensive Review

Abstract: Postpartum depression (PPD) is one of the three major categories on the spectrum of postpartum psychiatric syndromes. Postpartum psychiatric syndromes are classified as either postpartum blues, postpartum depression, or postpartum psychosis. Postpartum depression is important to recognize clinically because of the effect it can have on the mother-child bond. The neurosteroid allopregnanolone, a progesterone derivative, is important for its role in positively modulating GABAA receptors. GABA-mediated signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 41 publications
1
36
0
2
Order By: Relevance
“…In support, it has been previously reported that pretreatment with picrotoxin, bicuculline and flumazenil, antagonists of the GABA A receptor, block the anxiolytic- and antidepressant-like effects of chrysin [ 30 , 32 , 35 ]. In this sense, it is to possible suggest that the GABA A receptor is therefore a molecular target to the substances tested in the present experiment, chrysin [ 30 , 31 ], allopregnanolone [ 37 , 87 ], and diazepam [ 88 ], without discarding the participation of other systems of neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…In support, it has been previously reported that pretreatment with picrotoxin, bicuculline and flumazenil, antagonists of the GABA A receptor, block the anxiolytic- and antidepressant-like effects of chrysin [ 30 , 32 , 35 ]. In this sense, it is to possible suggest that the GABA A receptor is therefore a molecular target to the substances tested in the present experiment, chrysin [ 30 , 31 ], allopregnanolone [ 37 , 87 ], and diazepam [ 88 ], without discarding the participation of other systems of neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…ALLO is a potent positive allosteric modulator at the level of the synaptic and extrasynaptic GABA A receptors; thus, it contributes to the GABA-mediated inhibitory activity and inherently opposes glutamatergic excitatory activity [ 43 ]. Brexanolone, an exogenous formulation of ALLO, is rapidly effective in the treatment of PPD and is FDA approved for the treatment of PPD [ 44 ]. HRW are suspected of having maladaptive biological adjustments to physiological fluctuations of female hormones and their metabolites, especially ALLO [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ketamine enhances the mTOR complex 1 signaling and increases the number and function of synapses in the prefrontal cortex [ 42 ] independently of NMDA receptor inhibition [ 43 ]. Further drug developments include brexanolone, an analog of the neurosteroid THP, for the treatment of postpartum depression, as THP levels drop after pregnancy [ 44 ]. THP also affects the hypothalamus-pituitary-adrenal (HPA) axis as a positive allosteric modulator for specific subunits of extrasynaptic GABA A receptors (GABAARs) expressed in the paraventricular nucleus of the hypothalamus [ 40 ].…”
Section: Molecular Pathways and Systemsmentioning
confidence: 99%